2014
DOI: 10.1097/tp.0000000000000069
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Alternative Complement Pathway in Early Graft Loss After Intraportal Porcine Islet Xenotransplantation

Abstract: The alternative complement pathway contributes to the development of IBMIR and the early loss of grafts in NHPs with porcine ITx. Complement inhibition during the peritransplant period may be beneficial for the survival of islet grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 34 publications
2
47
0
Order By: Relevance
“…Very recently, a humanized CVF has been developed and confirmed its activity in a preclinical model without toxicity or immunogenicity (37). Moreover, we found that, upon intraportal infusion, adult pig islets activated the alternative pathway of the complement system, and that purified human factor H effectively prevented early islet loss as revealed by preservation of porcine C-peptide and reduced complement C3a and factor Bb (16). Therefore, we anticipate that successful replacement of anti-CD154 monoclonal antibody and introduction of purified human factor H or humanized CVF will allow us to replicate the results of this study in another set of monkey experiments and to begin clinical trials of pig islet transplantation in T1D patients.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Very recently, a humanized CVF has been developed and confirmed its activity in a preclinical model without toxicity or immunogenicity (37). Moreover, we found that, upon intraportal infusion, adult pig islets activated the alternative pathway of the complement system, and that purified human factor H effectively prevented early islet loss as revealed by preservation of porcine C-peptide and reduced complement C3a and factor Bb (16). Therefore, we anticipate that successful replacement of anti-CD154 monoclonal antibody and introduction of purified human factor H or humanized CVF will allow us to replicate the results of this study in another set of monkey experiments and to begin clinical trials of pig islet transplantation in T1D patients.…”
Section: Discussionmentioning
confidence: 77%
“…R080, R084, and R089 monkeys were insulin-independent for 168, 303, and 180 days, respectively. Blood glucose data for R080 and, R084 were partly presented under the identities of R10 and R11, respectively, in our recent study (for another purpose) (16). Absence of monkey C-peptide measured at intervals indicated that blood glucose control was entirely dependent on porcine C-peptide from the transplanted pig islets, but not on endogenous beta cell regeneration.…”
Section: Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…20 Although the use of MSCs has been accepted as one of the therapeutic approaches like other therapeutic cell therapies including pancreatic islets and hepatocyte and a number of successful reports have been published, the biocompatibility of MSC as well as of the other therapeutic cells still remain to be improved. Although systemic administration of anticoagulants and certain complement inhibitors are efficient in protecting the cells from thromboinflammation, [25][26][27][28][29] this treatment will increase the risk of bleeding in the patients. We have earlier reported that the expression of tissue factor on the cell surface triggers thromboinflammation, resulting in an early loss of the transplanted cells.…”
Section: Discussionmentioning
confidence: 99%
“…Strong complement activation has been observed during IBMIR [54]. In particular, activation of alternative complement pathway was profound in pig-to-NHP islet transplantation [55]. Following immediate responses by soluble inflammatory mediators, infiltration of islet grafts by large numbers of activated CD11b + neutrophils and macrophage was observed [56].…”
Section: Monitoring Of Cell-mediated Immune Responsesmentioning
confidence: 92%